PIS/PASEP, COFINS e EFD-contributions: application of legislation in tax accounting - perceptions of tax specialists - Ayres, Rosângela Mesquita; Szuster, Natan (Advances in Scientific and Applied Accounting, 2013)
The main objective of this study is to analyse the perception of tax specialists on the application of PIS/Pasep, Cofins and EFD-Contributions legislation in Tax Accounting. The study uses the hypothetical-deductive method, descriptive, bibliographical and field research and data collection through a questionnaire. The results show that tax specialists exhibited agreement bias that the tax obligations are impaired by excessive rules in the legislation (83%); by difficulty of interpreting the law (80%); by dispersion of information (80% ); by legislation complexity (94%); by the law frequently updating (98%); by the variety of schemes, tax rates and special situations (78%); by legal acts with immediate enforcement (80%) and by the input concept (83%). Regarding the EFD-contributions, the study records agreement bias to the statement that compliance with the tax obligation will require more knowledge (80%); it will take longer (74%) and it will be more complex (87%). Additionally, the study registers agreement bias that the legislation complexity creates additional costs for entities (85%) and to the statement that expansion of the input concept by Administrative Board of Tax Appeals - CARF facilitates the fulfillment of the tax (63%). The bibliographical research was confirmed in the field research by the perception of tax specialists, indicating urgent need to review the structure of the legislation related to PIS/Pasep and Cofins to make it fair to taxpayers and convenient for application in Tax Accounting.